SPIRITUALITY IN THE GLOBAL WORLD: INTERDISCIPLINARY ANALYSIS, CULTURAL CONDITIONING AND METHODOLOGICAL CHALLENGES - Насибуллов Камиль Исхакович (American Journals Publishing, 2024)
The article is devoted to the study of spirituality as an independent phenomenon located at the intersection of religiosity, culture and globalization. Particular attention is paid to the differences between religiosity and spirituality, as well as their relationship in the modern world. Key approaches to the study of spirituality, including perennialism and constructivism, are considered, which allows us to highlight the problem of universality and cultural conditionality of spiritual experience. The article analyzes the growing diversification of spiritual practices in the context of globalization, their impact on personal development, social processes and collective identity. The work emphasizes the importance of an interdisciplinary approach to the study of spirituality and opens up prospects for further research in psychology, sociology, and other sciences.
Keywords: Spirituality, religiosity, interdisciplinary approach, globalization, cultural conditioning, psychology of religion.